Influence of ligand substituent conformation on the spin state of an iron(ii)/di(pyrazol-1-yl)pyridine complex. Issue 10 (4th March 2021) - Kulmaczewski, Rafal; Howard, Mark J.; Halcrow, Malcolm A.
Abstract : The temperature of the solution-phase spin-crossover equilibrium in iron(ii ) complexes of 4-alkylsulfanyl-2, 6-dipyrazol-1-ylpyridine (bpp SR ) complexes depends strongly on the alkylsulfanyl substituent. Abstract : The temperature of the solution-phase spin-crossover equilibrium in iron(ii ) complexes of 4-alkylsulfanyl-2, 6-dipyrazol-1-ylpyridine (bpp SR ) complexes depends strongly on the alkylsulfanyl substituent. DFT calculations imply this reflects the conformation of the alkylsulfanyl groups, which lie perpendicular to the heterocyclic ligand donors in [Fe(bpp S t Bu )2 ] 2+ but are oriented co-planar with the ligand core for smaller SR substituents.